The History of the Awakening of the Ilava Community of Kerala - Jacob, George (My University, 1982)
The Ilavas are the largest community in Kerala. They were traditionally considered outside the pale of "varna" and treated as "untouchables' by the higher castes. A member of the community Sri Narayana Guru (1855-1927) and his disciples introduced religious and social reforms that brought in an awakening among the Ilavas at the beginning of the twentieth century. The changes among the Ilavas brought them into a series of escalating confrontations between themselves and the supporters of the caste-structure.
This thesis focuses on the transformations of the Ilava community and analyses how they now fit into the larger social structure. It asserts that the awakening of the Ilava community should be understood as a process of "modernization". It is described as modernization because it is an indigenous, historical and ongoing process in which people participate consciously. The Ilavas in their awakening have incorporated the values of modernity into their culture without losing the core-values of tradition. The history of the awakening of the Ilavas is a case of the modernization of a traditional society.
Keywords: Religion; Religion